2015
DOI: 10.4238/2015.december.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gemcitabine on radiosensitization, apoptosis, and Bcl-2 and Bax protein expression in human pancreatic cancer xenografts in nude mice

et al.

Abstract: ABSTRACT. The aim of this study was to evaluate the radiosensitizing effects of gemcitabine towards human pancreatic cancer xenografts. A human pancreatic cancer xenograft model was established in nude mice, 36 of which were randomly divided into 6 treatment groups. Tumors were measured every 2 days, and the tumor volumes, growth delays, and inhibition rates were compared to evaluate the gemcitabine enhancement factor. The apoptotic index was determined by terminal deoxynucleotidyl transferase dUTP nick end-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…B‐cell leukaemia/lymphoma‐2 family can be divided into anti‐apoptotic proteins and pro‐apoptotic proteins (Cory & Adams, ). Bcl‐2 and bax are the most representative proteins in Bcl‐2 family (Ghasemi et al, ; Shen, Wu, Wang, Li, & Zhu, ; Tenorio, Santana, Queiroz, Oliveira, & Queiroz, ), one inhibits apoptosis and the other promotes apoptosis, respectively, and play an important role in apoptosis induced by bisphenol A (Gong et al, ). There is a strong negative correlation between bax and bcl‐2, which is the main regulator of bcl‐2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…B‐cell leukaemia/lymphoma‐2 family can be divided into anti‐apoptotic proteins and pro‐apoptotic proteins (Cory & Adams, ). Bcl‐2 and bax are the most representative proteins in Bcl‐2 family (Ghasemi et al, ; Shen, Wu, Wang, Li, & Zhu, ; Tenorio, Santana, Queiroz, Oliveira, & Queiroz, ), one inhibits apoptosis and the other promotes apoptosis, respectively, and play an important role in apoptosis induced by bisphenol A (Gong et al, ). There is a strong negative correlation between bax and bcl‐2, which is the main regulator of bcl‐2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is one of the more effective drugs for sensitization of cells to radiation, because most pancreatic cancers do not respond to gemcitabine alone [1][2][3][4]. The radiosensitizing properties of gemcitabine have been demonstrated both in vivo and in vitro [5][6][7][8][9][10][11][12][13], although the detailed interaction of gemcitabine with radiation has not been elucidated. In preliminary experiments with human lung carcinoma cells, van Putten et al showed that gemcitabine treatment retards the rate and extent of DNA double-strand break (DSB) repair [14].…”
Section: Introductionmentioning
confidence: 99%